Acute kidney injury following colistin treatment in critically-ill patients: may glucocorticoids protect?. (17th February 2021) - Heybeli, Cihan; Canaslan, Kübra; Oktan, Mehmet Ası; Yıldız, Serkan; Arda, Hayri Üstün; Çavdar, Caner; Çelik, Ali; Gökmen, Necati; Cömert, Bilgin
Abstract : Nephrotoxicity following colistin administration is common and factors alleviating nephrotoxicity are yet to be determined. We retrospectively evaluated outcomes of subjects who were treated with colistin (n = 133) and with antibiotics other than colistin (control, n = 133) in intensive care units. Acute kidney injury (AKI) occurred in 69.2% and 29.3% of patients in colistin and control groups, respectively ( p < 0.001). In the colistin group, glucocorticoid exposure was more common in subjects who did not develop AKI ( p < 0.001). This was not the case in the control group. In the colistin cohort, older age (per 10 years, odds ratio [OR] 1.41, 95% CI 1.05–1.91; p = 0.025), PPI use (OR 3.30, 95% CI 1.18–9.23; p = 0.023) and furosemide treatment (OR 2.66, 95% CI 1.01–6.98; p = 0.047) were independently associated with the development of AKI while glucocorticoid treatment (OR 0.23, 95% CI 0.10–0.53; p = 0.001) was independently associated with reduced risk of AKI. Mortality was observed in 74 patients in the colistin cohort (55.6%). A higher APACHE-II score (OR 1.17, 95% CI 1.08–1.26; p < 0.001) was independently associated with mortality while a higher serum albumin level (per 1 g/dL increase, OR 0.20, 95% CI 0.070–0.60; p = 0.004) was associated with a lower risk of mortality. In conclusion, glucocorticoid exposure is associated with a lower risk of AKI caused by colistin therapy in critically-ill patients. Prospective studies are needed to confirm these findings and determine the optimal type, dose and duration of glucocorticoid therapy.